The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/fsn3.781
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer, antithrombotic, antityrosinase, and anti‐α‐glucosidase activities of selected wild and commercial mushrooms from Pakistan

Abstract: Mushrooms have been accepted as nutraceutical foods because of their high nutritional and functional values. They have also gained interest due to their medicinal properties, economic importance, and organoleptic merit. In this study, wild Ganoderma lucidum and four commercial mushrooms, that is, Pleurotus ostreatus, Volvariella volvacea, Hericium erinaceus, and Lentinus edodes from Pakistan were screened for their biological activities such as anticancer, antityrosinase, anti‐α‐glucosidase, and antithrombotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
1
11
0
2
Order By: Relevance
“…Sharif et al . (2018) determined in mushrooms aqueous extracts, IC 50 values against HT‐29 colon cancer cells around 100 μg mL −1 , whereas other mushroom extracts provided reduction of 20–40% in cell viability. Hu et al .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Sharif et al . (2018) determined in mushrooms aqueous extracts, IC 50 values against HT‐29 colon cancer cells around 100 μg mL −1 , whereas other mushroom extracts provided reduction of 20–40% in cell viability. Hu et al .…”
Section: Resultsmentioning
confidence: 98%
“…Antitumor activity of mushrooms and their extracts was also confirmed by other studies. Sharif et al (2018) determined in mushrooms aqueous extracts, IC 50 values against HT-29 colon cancer cells around 100 lg mL À1 , whereas other mushroom extracts provided reduction of 20-40% in cell viability. Hu et al (2018) reported lower IC 50 values for a phenolic-rich P. eryngii extract against HCT-116 cells, being 48.8 and 36.9 lg mL À1 at 48 and 72 h, respectively.…”
Section: Antiprolierative Potential Of the Extractmentioning
confidence: 95%
“…The newest study conducted in Pakistan studied the anti-proliferative effect of H. Erinaceus and other commercial mushrooms on cell line model, it confirmed the Anticancer, antithrombotic, anti-tyrosinase, and anti-αglucosidase activities of this mushroom. 24 In 2018 A Chinese study reported that erinacine which extracted from H. Erinaceus can promote apoptosis and inhibited cell proliferation by inducing MPTP opening and promote the release of cyt-C which plays a role in inhibiting the progression of Hepatocellular Carcinoma. 25 Further research showed that the extracts of H. Erinaceus given orally, have proved a tumor-suppressing activity similar to that of 5-fluorouracil, in the treatment of gastrointestinal cancers.…”
Section: The Role Of Lion's Mane Mushroom Mane In Cancermentioning
confidence: 99%
“…Wang ve ark. [10], G. lucidum'dan izole edilen ve bir triterpenoit olan Ganoderik asit-A'in insan hepatosellüler karsinom hücre hatlarına etkisini belirlemek üzere, farklı zaman dilimlerinde (24, 48 ve 72 saat) ve farklı konsantrasyonlarda (50,100,150,200,250 ve 300 µmol/L) yaptıkları uygulama sonucunda, 48 saat-100 µmol/L dozunda Ganoderik asit-A uygulamasının ardından HepG2 ve SMMC7721 insan hepatosellüler karsinom hücre hatlarının gelişimini önemli boyutta engellendiğini bildirmişlerdir. Ayrıca 72 saat 75 µmol/Ldozunda Ganoderik asit-A maruziyetinin benzer etki göstererek iki hücrenin de gelişimini önemli derece engellediği rapor edilmiş ve elde edilen sonuçlara göre en ideal tedavinin 100 ve 75 µmol/L olduğu öne sürülmüştür.…”
unclassified